A Novel Gene vp0610 Negatively Regulates Biofilm Formation in Vibrio parahaemolyticus - Jiang, Fufeng; Lei, Tao; Wang, Zhi; He, Min; Zhang, Jumei; Wang, Juan; Zeng, Haiyan; Chen, Moutong; Xue, Liang; Ye, Qinghua; Pang, Rui; Wu, Shi; et al. (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is an important foodborne pathogen and its biofilm formation ability facilitates its colonization and persistence in foods by protecting it from stresses including environmental variation and antibiotic exposure. Several important proteins are involved in biofilm formation; however, the identity and function of many remain unknown. In this study, we discovered a hypothetical protein, VP0610, that negatively regulates biofilm formation in Vibrio parahaemolyticus, and we found that the loss of vp0610 typically results in pleiotropic phenotypes that contribute toward promoting biofilm formation, including significantly increased insoluble exopolysaccharide production and swimming motility, decreased soluble exopolysaccharide production, and decreased bis-(3’-5’)-cyclic dimeric guanosine monophosphate production. Pull-down assays revealed that VP0610 can interact with 180 proteins, some of which (Hfq, VP0710, VP0793, CyaA) participate in biofilm formation. Moreover, deleting vp0610 enhanced the expression of genes responsible for biofilm component (flaE), the sugar phosphotransferase system (PTS) EIIA component (vp0793), and a high-density regulator of quorum sensing (opaR), while reducing the expression of the bis-(3’-5’)-cyclic dimeric guanosine monophosphate degradation protein (CdgC), resulting in faster biofilm formation. Taken together, our results indicate that vp0610 is an integral member of the key biofilm regulatory network of V. parahaemolyticus that functions as a repressor of biofilm formation.